The burden and care of orofacial cleft in Rwanda: a scoping review - Jimoh Amzat; Julienne Murererehe; Peace Uwambaye; Lauriyah Yusuf; Olusegun Olaopa; Afeez Salami; Ingabire Eliane Harerimana; Marie Claire Ineza; Eustache Ntigura; Jenipher Ober-Oluoch; Marie Aimee Dusenge; Dorcas Doree Nishimwe; et al. (BMC Oral Health)
Abstract Background Orofacial clefts (OFCs) are among the most common congenital anomalies accounting for over 4.6 million cases globally. In many developing nations, OFCs are associated with significant morbidity and a heightened risk of infant mortality due to barriers to accessing multidisciplinary care. This scoping review aims to identify knowledge gaps, establish research agendas, and inform decision-making for policy redirection in Rwanda regarding OFCs. Methods The design and reportage of this scoping review were based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Following the search of eleven electronic databases, all retrieved articles were imported into the Rayyan web application where deduplication of literature was done. One hundred and fourteen articles were obtained from the literature search. After screening and deduplication, six articles were included in the scoping review for data charting, collation, and summarization. Results Rwanda faces a substantial burden of OFCs, with prevalence rates ranging from 12.1 to 34.2% across its provinces. The scarcity of specialists who treat OFCs highlights a significant disparity in healthcare access. The prevalence of OFCs varies among demographics and age groups, with a higher incidence in males compared to females. This review also addresses the clinical management of OFCs in Rwanda, highlighting a low retention rate among patients receiving care. Conclusion This review highlights the need for targeted interventions in OFC care in Rwanda, including the early detection of associated anomalies, enhanced prenatal management, and improved access to specialized treatment facilities, particularly for patients with concomitant malformations. Policymakers and stakeholders must implement strategies to increase the number of specialists supporting individuals with OFCs and ensure high retention rates in OFC care. Further, OFC-related studies with representative sample sizes and advanced research designs are required to address the information gap and better inform Rwandan health policy.